D. Amélia: o preconceito racial em chove nos campos de cachoeira - BALIEIRO, Maria de Nazaré Vasconcelos (2021)
The present work has as theme "D. Amelia: the racial prejudice in rain in the fields of Cachoeira". The aim of this paper is to analyze the racial prejudice in the literature of Dalcídio Jurandir (1909-1979), in the book “Rain in the Campos de Cachoeira”. The purpose of the analysis demands the issue of racial prejudice, that is, racism, based on social relations of character and to know, through narrative, the truth of the less favored. Therefore, highlighting the denunciation of social ills in regionalist literature. The research had as methodology to the bibliographical analysis under the contributions of theorists Salles Vicente (1988); Maria Giacominis (1988) and Angela Daves (2016), among others. Therefore, an approach is taken about racial prejudice, social inequalities, lifestyle and the treatment imposed by a prejudiced society.